Trade Complexity and Growth under the Indonesia-Australia Partnership - Arif Darmawan; Latiffa Aurelien; Muhammad Farhan; Restu A. Suryaman (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2026)
Research Originality: This study contributes by linking Indonesia-Australia bilateral trade, economic complexity, and wholesale price dynamics within a single error-correction framework following the partnership's entry into force. Research Objectives: The study investigates the impact of exports, imports, economic complexity, merchandise trade openness, and wholesale prices on Indonesia's growth in both the short and long term from 2010 to 2025. Research Methods: Annual data are analyzed using Augmented Dickey-Fuller tests, Engle-Granger cointegration tests, and an error correction model, supported by residual diagnostics, for five bilateral trade variables. Empirical Results: The results indicate that all variables are associated with long-term development, while wholesale prices, imports, and exports primarily drive short-term fluctuations. Economic complexity is more significant as a structural channel than as an annual upheaval. Implications: These results suggest that Indonesia should focus on trade liberalization under the IA-CEPA, as it could serve as a real growth engine. Policy should move beyond trade volume targets by enhancing export diversification, stabilizing wholesale price transmission, and leveraging the partnership to strengthen skills, technology transfer, and higher-value-added production. JEL Classification: F13, F41, F62 How to Cite:Darmawan, A., Aurelien, L., Farhan, M., & Suryaman, R. A. (2026). Trade Complexity and Growth under the Indonesian-Australia Partnership. Signifikan: Jurnal Ilmu Ekonomi, 15(2), 327-338. https://doi.org/10.15408/sjie.v15i2.51348.